PENGARUH POLA KONSUMSI MASYARAKAT URBAN DAN DAMPAKNYA TERHADAP LINGKUNGAN - Tasya Jadidah, Ines; Anisah, Nia; Nabila Zakiyah, Andi; Kumala Sari, Elya; Dewi, Meyana; Panca Putri, Shabira (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
This study aims to investigate the influence of urban consumption patterns and their impact on the environment. Urban communities have different consumption patterns compared to rural communities, which are often more goods-oriented and consumptive in lifestyle. High consumption patterns in cities often lead to environmental problems such as increased waste production, air pollution, and overuse of natural resources. The research method involves surveying urban people to identify their consumption patterns, as well as analyzing the environmental impacts resulting from these consumption patterns. The results of this study can provide insights into the extent to which urban people's consumption patterns contribute to environmental change and provide a basis for the development of more sustainable policies. This research is expected to help governments, non-governmental organizations, and urban communities to better understand the impact of their consumption patterns on the environment, as well as encourage changes in consumption behavior that are more environmentally friendly. The conclusions of this study will provide valuable information in the effort to maintain a balance between urban development and environmental protection.